Case Report: Adjunctive hyperbaric oxygen therapy in pediatric glans reimplantation following penile trauma - Amoudi, Ramsey; Carreno-Galeano, Gabriel; Canalichio, Katie (Frontiers in Surgery, 2025)
Pediatric penile trauma is a rare urological emergency, and evidence-based guidelines for complex tissue salvage are limited. We report the case of an eight-year-old boy who presented six hours after sustaining a partial ventral glans avulsion. The patient underwent evaluation under general anesthesia followed by delayed surgical reimplantation of the avulsed glans tissue. As an adjunct to surgery, he received ten consecutive sessions of hyperbaric oxygen therapy (HBOT). Post-treatment follow-up demonstrated complete graft integration, excellent cosmetic outcome, preserved urinary function, and no complications. This case underscores the potential of HBOT to enhance graft viability and recovery in the setting of delayed reimplantation. Drawing on prior experience with graft-based reconstruction in complex hypospadias reoperations, HBOT may serve as a valuable adjunct in pediatric penile trauma involving complex tissue loss, offering a promising strategy to improve outcomes in similarly challenging reconstructive scenarios.